Modest Gains After an 8-Week Exercise Program Correlate With Reductions in Non-traditional Markers of Cardiovascular Risk - Liang, Grace; Huang, Xianxi; Hirsch, James; Mehmi, Sanjeev; Fonda, Holly; Chan, Khin; Huang, Ngan F.; Aalami, Oliver; Froelicher, Victor F.; Lee, David P.; Myers, Jonathan; Lee, Andrew S.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Although engaging in physical exercise has been shown to reduce the incidence of cardiovascular events, the molecular mechanisms by which exercise mediates these benefits remain unclear. Based on epidemiological evidence, reductions in traditional risk factors only accounts for 50% of the protective effects of exercise, leaving the remaining mechanisms unexplained. The objective of this study was to determine whether engaging in a regular exercise program in a real world clinical setting mediates cardiovascular protection via modulation of nontraditional risk factors such as those involved in coagulation, inflammation and metabolic regulation. Methods and Results We performed a prospective, cohort study in 52 sedentary patients with cardiovascular disease or cardiovascular risk factors at two tertiary medical centers between January 1, 2016 and December 31, 2019. Prior to and at the completion of an 8-week exercise program, we collected information on traditional cardiovascular risk factors, exercise capacity, and physical activity and performed plasma analysis to measure levels of fibrinolytic, inflammatory and metabolic biomarkers to assess changes in nontraditional cardiovascular risk factors. The median weight change, improvement in physical fitness, and change in physical activity for the entire cohort were: - 4.6 pounds (IQR: +2 pounds, -11.8 pounds), 0.37 METs (IQR: -0.076 METs, 1.06 METs), and 252.7 kcals/week (IQR: -119 kcals/week, 921.2 kcals/week). In addition to improvement in blood pressure and cholesterol, patients who lost at least 5 pounds, expended at least 1000 additional kcals/week, and/or achieved ≥ 0.5 MET increase in fitness had a significant reduction in plasminogen activator inhibitor-1 [9.07 ng/mL (95% CI: 2.78 ng/mL – 15.35 ng/mL); P=0.026], platelet derived growth factor beta [376.077 pg/mL (95% CI: 44.69 pg/mL – 707.46 pg/mL); P=0.026); and angiopoietin-1 [(1104.11 pg/mL (95% CI: 2.92 pg/mL – 2205.30 pg/mL); P=0.049)]. Conclusion Modest improvements in physical fitness, physical activity, and weight loss through a short-term exercise program was associated with decreased plasma levels of plasminogen activator inhibitor, platelet derived growth factor beta, and angiopoietin, which have been associated with impaired fibrinolysis and increased inflammation.